1994
DOI: 10.1111/j.1365-2591.1994.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic root‐end preparation Part 1. SEM analysis

Abstract: Preparations of apical cavities in resected root ends using rotary burs, with and without citric acid rinse, and ultrasonic tips were compared based on the presence or absence of superficial debris and smear layer. Three groups of 20 extracted teeth each were prepared as follows; I, a size 010 round bur was used to prepare an apical cavity 2-3 mm down the long axis of the root; II, treatment as per group I followed by a 60-s rinse with a solution of 10:3 (10% citric acid, 3% Fe2Cl3); and III, an ultrasonic ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 13 publications
1
80
0
Order By: Relevance
“…In the literature, there are some studies that compare the smear layer removal effectiveness of EDTA and CA; however, those findings are contradictory. Certain studies reported that 10% CA is more effective than EDTA (24,25); in contrast, some studies found no significant difference between them (23,26).…”
Section: Discussionmentioning
confidence: 91%
“…In the literature, there are some studies that compare the smear layer removal effectiveness of EDTA and CA; however, those findings are contradictory. Certain studies reported that 10% CA is more effective than EDTA (24,25); in contrast, some studies found no significant difference between them (23,26).…”
Section: Discussionmentioning
confidence: 91%
“…Root-end bevel is minimal or unnecessary, which decreases the number of exposed dentinal tubules (45,46). Cavity preparations are smaller and cleaner, cavities are deeper and more retentive, and the root-end cavity is better aligned with the long axis of the root canal (47,48). By reducing the risk of root perforation, ultrasonic instrumentation also provides significant advantages in treating deeply fluted roots when an isthmus is present (49,50).…”
Section: Root-end Cavity Preparationmentioning
confidence: 99%
“…13 Different concentrations (1-50%) have been proposed. 14 Gutmann et al 15 concluded that 10% citric acid is better than ultrasound for smear layer removal from the root end cavities. Yamaguchi et al 11 also…”
Section: Smear Layer Removalmentioning
confidence: 99%